The crystal cave - Stewart, Mary, 1916- (London : Hodder & Stoughton, 2012)
Follows Merlin, the magician, from his childhood in the court of the King of Wales until Arthur's birth.
Adult.
Adult
Keywords: Arthur, -- King -- Fiction; Arthur, -- King -- Fiction; Arthurian romances -- Adaptations; Britons -- Kings and rulers -- Fiction; Merlin (Legendary character) -- Fiction; Wizards -- Fiction; Arthurian romances; Historical fiction; Merlin (Legendary character) -- Fiction; Wizards -- Fiction; Great Britain -- Kings and rulers -- Fiction; Fantastic fiction; Fantastic fiction; Historical fiction